ANALYSIS OF METHODS AND PROSPECTS FOR APPLICATION OF OPTICAL METHODS FOR CONTROL OF WORKING SURFACES OF CYLINDER LINERS OF INTERNAL COMBUSTION ENGINES - Utaev, Sobir; Turaev, Abdugani (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Purpose of the study: analysis of methods for assessing wear and monitoring of new and worn cylinder liners of diesel and gas diesel engines D-243. During the research, the laws of the theory of lubrication, wear friction, as well as methods based on existing regulatory documents were used. As can be seen from the analysis results, the main share of the yield falls on metal particles.It has been established that the content of wear products in samples of engine oil running on gaseous fuel is less than in samples of engine oil running on diesel fuel. After a given operating time, the condition of the cylinder liners of a gas engine based on diesel engines was monitored. Using a bore gauge micrometer, measurements of the internal diameter were taken in 8-10 planes. The measurement results show deviations from the specified size.